Korelasi antara Kompetensi Kepribadian Guru dengan Minat dan Aktifitas Belajar Siswa di Madrasah Aliyah Samarinda - Rahmiyati, Yunik (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2016)
This research based on the phenomena on the field which are the correlation between the competence of teacher's personality and interests of student in learning activities on islamic education learning at Madrasah Aliyah (MA) in Samarinda. The aim of the research is to descript the competence of the teacher’s personality, interest of student in learning activities. Therefore, to identify how much the correlation between the competence of the teacher's personality and interests of student in learning activities partially is and to identify how much the correlation between the competence of the teacher's personality and interests of student in learning activities on Islamic education learning at Madrasah Aliyah (MA) in Samarinda. The result showed that sBoth competence of teacher’s personality and students learning activity had a very strong correlation about r=0.989 which mean the competence of teacher’s personality, student’s interest and learning activity had an average correlation about 97.8% and the rest of 2.2% was defined in other variables. The hypothesis showed that there was a significance correlation between competence of teacher’s personality and the learning activity were accepted as true by value (Fcount = 4246.876 ; sig. = 0,000).